Borrelia burgdorferi 0755, a Novel Cytotoxin with Unknown Function in Lyme Disease - Sam T. Donta (Toxins, 2024)
The pathophysiology of Lyme disease, especially in its persistent form, remains to be determined. As many of the neurologic symptoms are similar to those seen in other toxin-associated disorders, a hypothesis was generated that B. burgdorferi, the causative agent of Lyme disease, may produce a neurotoxin to account for some of the symptoms. Using primers against known conserved bacterial toxin groups, and PCR technology, a candidate neurotoxin was discovered. The purified protein was temporarily named BbTox, and was subsequently found to be identical to BB0755, a protein deduced from the genome sequence of B. burgdorferi that has been annotated as a Z ribonuclease. BbTox has cytotoxic activity against cells of neural origin in tissue culture. Its toxic activity appears to be directed against cytoskeletal elements, similar to that seen with toxins of Clostridioides difficile and Clostridioides botulinum, but differing from that of cholera and E. coli toxins, and other toxins. It remains to be determined whether BbTox has direct cytotoxic effects on neural or glial cells in vivo, or its activity is primarily that of a ribonuclease analogous to other bacterial ribonucleases that are involved in antibiotic tolerance remains to be determined.